(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Siddha system of medicine is the eternal science of life. It is a system that has its extensive bonding with Dravidian culture, language and beliefs. The system of medicine mostly prevailed and prospered in the regions of Dravidian cultures by the great Siddhars. It’s unique as one only than other AYUSH traditional systems of medicine across India with its distinctive abundant usage of medicinal plants, metals, minerals and animal products. Siddhars used the steps of Alchemy to prepare various medicines from metallic and mineral origin for attainment elixir and various rare diseases. Siddha medicine is classified into 32 types of internal and external medicine each. Among the 32 types of internal medicine Chendhuram is a medicine shelf life of 75 years usually from herbo-mineral combinations. Arumuga Chendhuram (ARC) is a herbo-mineral formulation cited in Siddha literature ‘Siddha Vaithiya Thirattu’. ARC was orally administered at higher dose 2gm/kg to the Wistar Albino rats in acute toxicity study and during 28 days of repeated (sub acute) toxicity study, at daily doses of 12, 24 & 48mg/kg of body weight to the Wistar Albino rats. Type II collagen arthritis is another model for developing autoimmune arthritis. The immune pathogenesis mediated by T cell and B cell response to collagen. By this model, nearly 100% arthritis can be achieved. In our study, ARC after 42 days treatment reduced the arthritic swelling significantly and degree of inflammation evident to act against auto immune disorder.